In vitro dissolution of acidulated rock phosphate by phosphate solubilizing microorganisms (2015)
The low availability of phosphorus (P) in the soil and the high cost of P fertilization are factors that limit agricultural productivity. A biotechnological alternative for to handle this problem is to use soil microorganisms capable of dissolving rock phosphate (RP), thus improving its effectiveness as a P fertilizer. This study was carried out with the objective of determining the effectiveness of Aspergillus niger –As-, Penicillium sp. –Pn-, Bacillus sp –B-. and an unidentified actinomycete –At- in the in vitro dissolution of two partially acidulated rock phosphates. The treatments consisted of 2x16 factorial arrangement [2 levels of RP: either Boyaca RP or Norte de Santander RP; 16 levels of inoculum: an uninoculated control, individual inoculations (with As, Pn, B, At), dual inoculations (AsPn, AsB, AsAt, PnB, PnAt, BAt), triple inoculations (AsPnB, AsPnAt, AsBAt, PnBAt), and quadruple inoculation (AsPnBAt)]. Each treatment was replicated three times. It was found that the microbial effectiveness in the in vitro dissolution of RP depended on the type of RP, the composition of the inoculum used and the interaction of both factors. The best results were obtained with the Norte de Santander RP and A. niger used alone. When this fungus combined with the other microorganisms, its capacity to dissolve RP was significantly reduced.